PERSEPSI MASYARAKAT PERKOTAAN TERHADAP PENTINGNYA FUNGSI RUANG TERBUKA HIJAU (RTH) DI KOTA PONTIANAK - Januarisa, Dela Valenia; Hardiansyah, Gusti; Fahrizal, . (JURNAL HUTAN LESTARI, 2016)
The grew of urban communities caused the needs of population increased and followed by increasing of facilities and infrastructure for balenced the fulfillment of urban comunities. And this cause the shift of vegetation in urban areas, so that the vegetation cover were decreases. This study aimed to observe the area of green open space in Pontianak and analyze public perception of the importance of the function of urban green open space in Pontianak, this research is expected to help the government to manage of green open space (RTH) in Pontianak, and provide information to the public about the importance function of the green open space in Pontianak, and can be used as material for further research. This study used a qualitative approach with descriptive survey method by interview and questionnaire tools. Sampling was done by purposive sampling (random sampling with the desired state) by 90 respondents that representing 10% of the 857 households. The result of the reseach can be concluded the public perception may be the potential success of program development and management of green open space in Pontianak. Community participation in the management and development of green open space is very important. This effort to prevent irregularities utilization of space. Management and development of green open space Pontianak need to be developed and preserved as Pontianak greening efforts and overcome the levels of noise and dust pollution that growing by day.Keywords: Urban Society, green open space